If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15.94*60+13.64*x=(60+x)*15
We simplify the equation to the form, which is simple to understand
15.94*60+13.64*x=(60+x)*15
Reorder the terms in parentheses
+956.4+13.64x=(+900+15x)
Remove unnecessary parentheses
+956.4+13.64x=+900+15x
We move all terms containing x to the left and all other terms to the right.
+13.64x-15x=+900-956.4
We simplify left and right side of the equation.
-1.36x=-56.4
We divide both sides of the equation by -1.36 to get x.
x=41.470588235294
| x^2+5x-3 | | 23x+13=22x+25 | | -2/x+x=-1 | | x-12=0,6x | | 15+4x+18x=19x-4+3x | | 4x-5-x=7+x-2 | | 2*(3x-1)=8x-4 | | 5x+=12+2x | | 3x-26+2x+70+5x-10+3x+2x+56=540 | | 4x(16-12)+x=2x-1 | | 5(x-2)+x=12-3 | | x(5-3)+6=15+2x | | x(x-1)-4=(x-3)(x+3)-x | | (13)+(56)= | | 0=2x^2+4x-5 | | 11-3z=-4 | | 5x-(9-3x)=-19+2(x-4) | | 32x+1=130 | | 109x+1=55x | | 2(x+3)-3(2x-4)=2(x-3) | | x,6-1,6=1 | | 0.9/10= | | 4(11x+40)=77x+28 | | 14x-1+92+105=-4+14x | | 125=26x+3 | | 2x-3=12x+x | | 43-92x=5 | | .05*x^2-45*x-675=0 | | 5*x+x=300 | | 2*x-4=18 | | x+x+x=3*x | | 2*x-5=3 |